2022
DOI: 10.1177/1532673x221112395
|View full text |Cite
|
Sign up to set email alerts
|

Donald Trump’s Effect on Who is Considered “Conservative”

Abstract: Conservative intellectuals have expressed concern that Donald Trump has tarnished the conservative brand with his authoritarian-populist rhetoric and style of governing. What exactly is Donald Trump’s effect on this ideological label? In this paper I replicate work showing that members of Congress who have openly supported Trump are seen as more conservative than those who do not openly support him. I then test this relationship experimentally and explore whether a pro (or anti) Trump cue alone drives this per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Lenz (2012) showed that voters often choose a candidate for non-ideological reasons and subsequently adjust their views to align with their preferred candidate's stances. Previous research considered the ideological effect of Trump on the Republican Party and its voters, finding that Trump-aligned politicians were perceived as more conservative (Amira 2022;Hopkins and Noel 2022). Conservative voters have expressed a willingness to support liberal policy stances when Trump is behind them, revealing that his endorsements can supersede the impact of ideological cues (Agadjanian 2021;Barber and Pope 2019).…”
Section: Theorymentioning
confidence: 99%
“…Lenz (2012) showed that voters often choose a candidate for non-ideological reasons and subsequently adjust their views to align with their preferred candidate's stances. Previous research considered the ideological effect of Trump on the Republican Party and its voters, finding that Trump-aligned politicians were perceived as more conservative (Amira 2022;Hopkins and Noel 2022). Conservative voters have expressed a willingness to support liberal policy stances when Trump is behind them, revealing that his endorsements can supersede the impact of ideological cues (Agadjanian 2021;Barber and Pope 2019).…”
Section: Theorymentioning
confidence: 99%
“…6 Thus, they often self-identify with ideological labels only symbolically rather than substantively (Conover and Feldman, 1981;Ellis and Stimson, 2012). The latest research also suggests that many Black respondents are unfamiliar with the terms "liberal" and "conservative" (Jefferson, forthcoming) and that public understandings of ideological terms could be reoriented by political elites (Amira, 2022;Hopkins and Noel, 2022). If the public lacks a basic understanding or has a different 5 For instance, the existing literature has demonstrated that individual attachment to the liberal or conservative identity can meaningfully shape political attitudes and behavior (e.g., Popp and Rudolph, 2011;Neiheisel, 2016;Rogowski and Sutherland, 2016;Mason, 2018).…”
Section: Potential Problems Of Self-reported Ideologymentioning
confidence: 99%